Identification of Per a 13 as a novel allergen in American cockroach. (March 2022) - Xu, Zhi-Qiang; Zhu, Li-Xiang; Lu, Chen; Jiao, Yong-Xin; Zhu, Dan-Xuan; Guo, Miao; Yang, Yong-Shi; Cao, Meng-Da; Zhang, Li-Shan; Tian, Man; Sun, Jin-Lyu; Wei, Ji-Fu
Graphical abstract: Highlights: Per a 13 was firstly identified as a novel family of allergen in American cockroach. The full-length cDNA encoding Per a 13 was firstly isolated. Both nPer a 13 and rPer a 13 were purified and characterized. Among the patients, 49.3 % were reacted to Per a 13. Patients with allergic rhinitis were more sensitized. Abstract: Background: Cockroaches are an important source of indoor allergens. Environmental exposure to cockroach allergens is closely associated with the development of immunoglobulin E (IgE)-mediated allergic diseases. However, the allergenic components in the American cockroaches are not fully studied yet. In order to develop novel diagnostic and therapeutic strategies for cockroach allergy, it is necessary to comprehensively investigate this undescribed allergen in the American cockroach. Methods: The full-length cDNA of the potential allergen was isolated from the cDNA library of the American cockroach by PCR cloning. Both the recombinant and natural protein molecules were purified and characterized. The allergenicity was further analyzed by enzyme linked immunosorbent assay, immunoblot, and basophil activation test using sera from cockroach allergic patients. Results: A novel allergen belonging to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was firstly identified in the American cockroach and named as Per a 13. The cDNA of this allergen is 1255 base pairs in length and contains an open reading frame of 999 base pairs, encoding 332 amino acids. The purified Per a 13 was fully characterized and assessed to react with IgEs from 49.3 % of cockroach allergic patients, and patients with allergic rhinitis were more sensitized to it. Moreover, the allergenicity was further confirmed by immunoblot and basophil activation test. Conclusions: We firstly identified GAPDH (Per a 13) in the American cockroach, which is a novel type of inhalant allergen derived from animal species. These findings could be useful in developing novel diagnostic and therapeutic strategies for cockroach allergy.